Shemale as the discriminated LGBT in the film 'Bulu Mata' - Wayrooy, Nanda Dwi Puspita; Kurnia, Ari (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2022)
The existence of shemale (transgender from male to a female) is still taboo in Indonesia, especially in less developed areas. This article sheds light on how Bulu Mata, as a documentary film, represents shemale discrimination as an LGBT group minority. Using the Peircean semiotics method, we dissected 27 scenes about transgender discrimination in Bulu Mata and analyzed them in the representamen, object, and interpretant stages. We found three verbal harassment, twenty scenes showing ostracized transgender, and three scenes of physical violence experienced by shemale. Intertextually, we also found media documents (both conventional and social media) that captured, reported, and retold various Shemale activities in some areas of Indonesia. Still, the contents and messages were widely discriminated against by the public who watched them.